Pengaruh Identitas Merek dan Kesadaran Merek Terhadap Kepercayaan Merek Pada Bank Muamalat Cabang Pembantu Kolaka - Sri Rahayu Baharuddin; Fitri Kumalasari; Almansyah Rundu Wonua (Global Leadership Organizational Research in Management, 2023)
This study aims to determine: (1) the effect of brand identity on brand trust at Bank Muamalat Kolaka Sub-branch. (2) brand awareness of the brand trust at Bank Muamalat Kolaka Sub-branch. This study uses a quantitative method approach. Collecting data in this study using literature, observation, questionnaires and documentation. The sample in this study was 100 customers of Bank Muamalat, Kolaka Branch. Testing the research instrument using the validity test and reliability test with SPSS. The data analysis technique used in this study is the measurement model test (outer model) and the structural model test (inner model) with Smart PLS. Based on the results of the study it is known that the first hypothesis, there is a positive and significant influence between constructs of brand identity variables on brand trust in Bank Muamalat Kolaka Sub-branch. The second hypothesis, there is a positive and significant influence between the construct variable brand awareness on brand trust of Bank Muamalat Kolaka Sub-branch.